Evaluation of matrix effects in the analysis of volatile organic compounds in whole blood with solid‐phase microextraction. Issue 23 (22nd October 2013) - Alonso, Monica; Castellanos, Mar; Sanchez, Juan M.
<x xml:space="preserve">Abstract</x> The complexity and matrix variability of biological samples requires an accurate evaluation of matrix effects. The dilution of the biological sample is the simplest way to reduce or avoid the matrix effect. In the present study, a set of volatile organic compounds with different volatilities was used to assess the effect of the dilution of blood samples on the extraction efficiency by headspace solid‐phase microextraction. It was found that there was a significant matrix effect but that this effect differs significantly depending on the volatility of the compound. A 1:2 (blood/water) dilution was enough to allow quantitative recoveries of those compounds with boiling points <100°C. For compounds with boiling points between 100 and 150°C, the matrix effect was stronger and a 1:5 dilution was required. The dilution of blood samples proved to be inefficient for quantitative recovery of compounds with boiling points >150°C. A 1:5 dilution of the sample allowed detection limits in the range of nanogram per liter to be obtained. This was sufficient to detect the main volatile compounds present in blood and contamination after exposure.